La Historia entre paréntesis. Una lectura de Un día de éstos de Gabriel García Márquez - Fernando Moreno (Caravelle)
This contribution is the reading of Gabriel García Márquez’s tale «One of these days» (included in the collection Los funerales de la Mamá Grande, 1962) that aims to show the functioning of some of its speeches, themes and organizations, as well as their links with the meanings put at stake by the text.The text’s brevity, its apparent simplicity, hides and reveals official truths and intimate ones; its framework, its contrasts, dualities, correspondences and repetitions achieve a sober speech, meagre with its pretended candour, just like the main character, but that enlightens and lashes abundantly and strongly the lack of balance of a History that the tale stages inside significant brackets.